Will There Be a Science of Law in the Twenty-First Century? - Stith, Richard (Revue générale de droit)

(untitled) (Éditions Wilson & Lafleur, inc., 1991)
The skepticism of the American Legal Realists and their heirs threatens to make a politically neutral science of law impossible and thus to undermine the liberal polity which needs such a science. Ronald Dworkin attempts to refute the skeptics and defend both legal theory and liberalism. However, the author points out, Dworkin and liberalism are themselves skeptics when it comes to moral principles, and, therefore, they cannot wholly escape from similar skepticism with regard to legal principles. Both Anglo-American and Continental legal history are examined in the course of these arguments.